2017
DOI: 10.1016/j.neubiorev.2016.12.037
|View full text |Cite
|
Sign up to set email alerts
|

The BTBR mouse model of idiopathic autism – Current view on mechanisms

Abstract: Autism spectrum disorder (ASD) is the most commonly diagnosed neurodevelopmental disorder, with current estimates of more than 1% of affected children across nations. The patients form a highly heterogeneous group with only the behavioral phenotype in common. The genetic heterogeneity is reflected in a plethora of animal models representing multiple mutations found in families of affected children. Despite many years of scientific effort, for the majority of cases the genetic cause remains elusive. It is there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
112
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(116 citation statements)
references
References 126 publications
4
112
0
Order By: Relevance
“…We have validated that they also exhibit the psychiatric comorbidity of ASD, including anxiety and attention deficit [15]. Additionally, these mice share similarities of anatomical changes with ASD patients [16], strengthening their applicability as an animal model for studying idiopathic autism [17].…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…We have validated that they also exhibit the psychiatric comorbidity of ASD, including anxiety and attention deficit [15]. Additionally, these mice share similarities of anatomical changes with ASD patients [16], strengthening their applicability as an animal model for studying idiopathic autism [17].…”
Section: Introductionmentioning
confidence: 63%
“…Despite being an established model for ASD, the genetic aspects of BTBR mice underlying their autistic-like behaviors are unclear. Multiple gene mutations with characteristic DNA polymorphisms in BTBR [17,57] have made it difficult to map out the molecular basis for the aberrant presynaptic and postsynaptic excitability at the IN-PN synapses. Informed by an essential role of Kv1.2 in controlling the presynaptic excitability [43][44][45][46][47] and downregulation of Kv1.2 by deletion of Fmr1 [31], we probed Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Both sets have been processed through the pipelines described above. Several groups have studied the BTBR strain as a model of autism (Meyza & Blanchard, ; Scattoni, Gandhy, Ricceri, & Crawley, ). Previous MR studies of the BTBR have shown changes in white matter FA and reduced neuroanatomical volumes, including an absent corpus callosum and a reduced hippocampal commissure (Ellegood, Babineau, Henkelman, Lerch, & Crawley, ).…”
Section: Resultsmentioning
confidence: 99%
“…Comparison of tractography within the forelimb representation of the right primary somatosensory cortex in two murine strains (individual specimens): C57BL/J6 (a), a common mouse model in biomedical research, and BTBR (b) a murine model that bears phenotypic resemblance to human autism spectrum disorders (Meyza & Blanchard, ; Scattoni et al, ). Images to the far left and right in (a) and (b) show tractography as seen from the dorsal aspect of the mouse brain; insets localize the forelimb representations.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the pharmacologically induced VPA model and the Shank3B genetic model, the BTBR inbred mouse strain is another valid model of ASD that has been used to represent idiopathic autism. The BTBR model displays various genetic, neuroanatomic, and molecular irregularities [5], including altered neurotrophic brainderived factor (BDNF), the absence of the corpus callosum, and an imbalance in the excitatory/inhibitory (E/I) ratio [6]. Furthermore, the BTBR exhibits three unique and vigorous behavioral features that characterize ASD: deficits in social communication among both the young and adults, an uncommon ultrasonic utterance in newborns, and recurring fixed grooming behaviors [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%